تأثير بعض المؤشرات الاقتصادية على أداء أسواق الأوراق المالية لدول المغرب العربي - بوزغوب, مريم; عيسى, نجاة (جامعة الوادي - University of Eloued, 2023)
تسعى هذه الورقة البحثية الى تحديد تاثير بعض المتغيرات الاقتصادية على أداء اسواق الاوراق المالية المغاربية بتطبيق نموذج قياسي وقد تم التوصل الى وجود علاقة معنوية في المدى الطويل لكل من مؤشرات معدل النمو الإقتصادي والتضخم على مؤشرات اداء اسواق الاوراق المالية والممثلة في القيمة السوقية وحجم التداول و مؤشر السوق بنسب متفاوتة حسب المستوى الاقتصادي لكل من دولة الجزائر، تونس والمغرب. This research paper aims to indicate the impact of a number of economic variables on the Maghreb Securities Market performance by applying a standard model, and accordingly, a long-term ethical relationship has been found. This relationship between indicators of economic growth rate, and inflation in the index of Securities market performance represented in the market value, the volume of trade and the market index, all of which are at different rates based on the economic level of each country، Algeria, Tunisia and Morocco.
The impact of some economic indicators on the performance of the securities markets in the Arab Maghreb countries
مقال
Keywords: أداء اسواق الاوراق المالية ، معدل النمو الإقتصادي ، معدل التضخم ، مؤشرات اداء اسواق الاوراق المالية.; Securities market performance, economic growth rate, inflation rate, index of Securities market performance